Solid-phase combinatorial synthesis using microarrays of microcompartments with light-induced on-chip cell screening. (June 2019) - Rosenfeld, A.; Brehm, M.; Welle, A.; Trouillet, V.; Heissler, S.; Benz, M.; Levkin, P.A.
Abstract: The process of drug discovery includes individual synthesis and characterization of drug candidates, followed by a biological screening, which is separated from synthesis in space and time. This approach suffers from low throughput and associated high costs, which in turn lead to inefficiency in the field of drug discovery. Here, we present a miniaturized platform combining combinatorial solid-phase synthesis with high-throughput cell screenings. The method is based on the formation of nanoporous poly(2-hydroxyethyl methacrylate- co -ethylene dimethacrylate) layers patterned with hydrophilic spots separated from each other by superhydrophobic liquid-impermeable barriers. The porous polymer inside the hydrophilic spots is used as a support to conduct solid-phase synthesis. The hydrophilic spots can be then filled with droplets containing either reagents for synthesis or live cells. Upon irradiation with UV light, products of solid-phase synthesis are released from the porous polymer because of the photo-cleavable linkers used and diffuse into separate droplets. The light-induced release of the products allows the control of the release spatially, temporally, and quantitatively. To demonstrate the versatility and usability of the platform for various cell lines, we have successfully implemented peptide synthesis to create an exemplary chemical library and demonstrated high cell viability after the UV-triggered small-molecule release.